1976
DOI: 10.1136/pgmj.52.606.234
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic accessory lobe of liver with a review of the literature

Abstract: SummaryAn accessory lobe of the liver with long well defined mesentery presenting as recurrent pain in abdomen in a Hindu female is described. This is the seventh case recorded in English literature. The embryological genesis of this anomaly and the possibility of preoperative diagnosis by various techniques is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 8 publications
0
31
0
2
Order By: Relevance
“…Presence of a large symptomatic accessory liver lobe was found in a woman aged 70 years by Llorente & Dardik (1971). Pujari & Deodhare (1976) have reported the presence of a symptomatic accessory lobe. The accessory lobes may herniate into the thorax through the diaphragm and cause serious problems (Feist & Lasser, 1959), Joshi et al (2009) did an extensive study on variations of the liver.…”
Section: Discussionmentioning
confidence: 90%
“…Presence of a large symptomatic accessory liver lobe was found in a woman aged 70 years by Llorente & Dardik (1971). Pujari & Deodhare (1976) have reported the presence of a symptomatic accessory lobe. The accessory lobes may herniate into the thorax through the diaphragm and cause serious problems (Feist & Lasser, 1959), Joshi et al (2009) did an extensive study on variations of the liver.…”
Section: Discussionmentioning
confidence: 90%
“…As a type of congenital anatomical malformation, ALL occurs very rarely because it is associated with an autosomal recessive gene with a very low frequency. Anatomical research through necropsies of 172 rats confirmed this genetic theory (8). Currently, there are two hypotheses of the mechanism of an ALL: (i) the embryonic liver curls outwards and forms an accessory lobe during the embryonic stage of development (10) or (ii) an accessory lobe arises from intra-abdominal hypertension caused by the development of the tunica muscularis recti and the enlargement of the liver (11).…”
Section: The Mechanism Of Allmentioning
confidence: 97%
“…During the 7th and the 8th week of embryo development, which is when the muscular layer of the abdominal wall is formed, development of an ALL in the embryo may obstruct the closing of the umbilical ring (3,10), which is why most ALLs are associated with acromphalus. ALLs are also associated with congenital biliary atresia (22), congenital diaphragmatic defects, and angiocavernoma (8). Most reported cases of an ALL involve females ranging in age from newborns to 75 years.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…2 Ectopic liver tissue occasionally causes unexpected clinical problems. [6][7][8] We encountered two patients with an ectopic liver; in one patient, ectopic liver tissue in the stomach developed hepatocellular carcinoma (HCC) while the mother liver had no HCC, and in the other patient with cirrhosis, who died in an automobile accident, an ectopic liver attached to the gallbladder had cirrhosis histologically. A review of the literature revealed more than 20 cases of HCC arising outside the liver, mainly from Japan.…”
mentioning
confidence: 99%